Bactericidal activity of textile with copper thread against antibiotic-resistant and carbapenemase-producing bacteria that cause nosocomial infections. - Domínguez Salvador, Julitza Yanet (2024)
Introduction: Hospital-acquired infections  (HAI) due to antibiotic-resistant bacteria are a public health problem, and the hospital environment is a favorable reservoir for various pathogens, therefore a health option for pathogen control is to evaluate the bactericidal activity of textile platforms with yarn copper against pathogens that cause carbapenemase-resistant HAI. Materials and methods: the bactericidal capacity of the biomedical textile with and without copper thread was evaluated in four bacterial strains: Escherichia coli, Pseudomonas aeruginosa, Klebsiella peumoniae and Staphylococcus aureus. Differences in survival time and bacterial density were established using ANOVA and Tukey tests with a significance level of P <0.05 in triplicate. Results: The survival of E. coli, K. pneumoniae, P. aeruginosa and S. aureus, on biomedical textiles with copper thread, was 80, 90, 120 and 140 min, respectively. But in textile without copper thread the bacterial density (1x105 CFU/ml) remained viable for more than 180 min for all bacterial strains. Copper thread textile is more effective in eliminating Gram-negative bacteria (K. pneumoniae, P. aeruginosa, E. coli), versus Gram-positive bacteria (S. aureus). Conclusion: the textile with copper thread has an antibacterial effect against K. pneumoniae, P. aeruginosa, S. aureus and E. coli; Unlike textiles without copper, where bacteria remained viable, copper thread has potential as an antimicrobial against carbapenemase-resistant pathogens to be applied in biomedical textile platforms or dressings.